2015
DOI: 10.1016/j.ab.2015.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis-coupled flow cytometry for detection and size discrimination of anionic polystyrene particles

Abstract: Flow cytometry was evaluated for its capacity to detect and distinguish a wide size range (20-2000 nm) of fluorescent polystyrene particles (PSPs). Side scatter and fluorescence parameters could predict dispersed PSP sizes down to 200 nm, but the forward scatter parameter was not discriminatory. Confocal microscopy of flow-sorted fractions confirmed that dispersed PSPs appeared as a single sharp peak on fluorescence histograms, whereas agglomerated PSPs were detected as smaller adjacent peaks. Particles as sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…The ingestion of particles has in principle been reported for sizes up to 10 µm for J774A.1, but particle surface modifications with e.g. IgG or carboxyl groups were necessary in such cases, and ingestion rates were still rather low 43 , 68 , 70 72 . For the liver macrophage cell line ImKC, a similar trend as for J774A.1 was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The ingestion of particles has in principle been reported for sizes up to 10 µm for J774A.1, but particle surface modifications with e.g. IgG or carboxyl groups were necessary in such cases, and ingestion rates were still rather low 43 , 68 , 70 72 . For the liver macrophage cell line ImKC, a similar trend as for J774A.1 was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Because PBMCs are composed by both monocytes and lymphocytes, we evaluated by flow cytometry the ability of the different cell subpopulations to interact with TiO 2 particles. This approach, based on SSC signal intensity, has been applied successfully in several studies indicating its suitability for this purpose (Mutzke, Chomyshyn, Nguyen, Blahoianu, & Tayabali, ; Suzuki, Toyooka, & Ibuki, ; Zucker et al, ). Data clearly indicated that TiO 2 particles interacted mainly with the monocyte cell subpopulation, with negligible interaction with the lymphocyte subpopulation (Herd et al, ; Thurn et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As compared to peripheral tissue macrophages, microglia have lower phagocytic capacity which can be augmented following activation by pro-inflammatory stimuli ( 14 , 15 ). Measurement of phagocytic capacity of microglia can be performed by in vitro engulfment assays using fluorescent probe-labeled particles, Aβ aggregates, opsonized bacteria, or latex particles followed by immunofluorescence microscopy ( 14 , 16 , 17 ). These assays can introduce sampling biases by exclusion of non-adherent cells in a cell type-like BV2 that has significant proportions of live floating cells.…”
Section: Introductionmentioning
confidence: 99%